Prognostic Value of Germline DNA Repair Gene Mutations in De Novo Metastatic and Castration‐Sensitive Prostate Cancer. (19th March 2020) - Wei, Yu; Wu, Junlong; Gu, Weijie; Wang, Jun; Lin, Guowen; Qin, Xiaojian; Dai, Bo; Gan, Hualei; Ye, Dingwei; Zhu, Yao
Abstract: Background: Germline DNA damage repair gene mutations (gDDRm) have been found in approximately 12% of patients with metastatic prostate cancer (mPCa). Previous studies of the clinical impact of gDDRm have mainly been in the setting of metastatic castration‐resistant prostate cancer (mCRPC). This study aimed to determine the prognostic value of gDDRm in de novo metastatic and castration‐sensitive prostate cancer (mCSPC). Materials and Methods: We retrospectively collected the records of 139 consecutive men with de novo mCSPC who initially received systemic therapies following guidelines. This included 128 patients who underwent genetic testing at our center and 11 patients referred to our center after being identified as gDDRm carriers. Time to mCRPC was collected. Kaplan‐Meier and log‐rank analysis were used to analyze the association between gDDRm and clinical outcomes. Survival outcomes were adjusted using multivariable Cox regression models. Results: Of the 139 patients with de novo mCSPC, 28 gDDRm carriers were identified. Median time progressing to mCRPC was significantly shorter in patients carrying gDDRm than in those without mutations (8.3 vs 13.2 months; hazard ratio [HR], 2.37; p < .001). Moreover, median progression time was almost halved in BRCA2 carriers (6.3 vs. 13.2 months; HR, 3.73; p < .001). Subgroup analysis revealed that the presence of gDDRm indicated poor therapy response regardless of disease volume and prostate‐specific antigen nadir within the first 7 months. Presence of gDDRm remained independently associated with increased risk of progression to mCRPC in multivariate analysis (adjusted HR, 1.98; p = .006). Conclusion: Our study suggested that positive gDDRm status predicted rapid progression to castration resistance in patients with de novo mCSPC. We propose identifying gDDRm status at the time of diagnosis for mCSPC patients, considering it is the first step of tailoring individualized treatment. In addition, DNA repair genes were a good therapeutic target for poly (ADP‐ribose) polymerase inhibitors, and our results call for more frontline targeted therapy trials in gDDRm carriers to prolong the progression time. Implications for Practice: Results of this study suggested that positive germline DNA damage repair gene mutation (gDDRm) status predicted earlier progression to castration resistance in patients with de novo metastatic and castration‐sensitive prostate cancer (mCSPC). These findings indicated the importance of intense therapy for some subgroups of mCSPC, especially for mCSPC harboring gDDRm with low‐volume disease. Moreover, gDDRm was a good therapeutic target for poly (ADP‐ribose) polymerase inhibitors, and these findings call for more molecular marker driven trials moving to the mTNPC setting. Abstract : There is increasing interest in defining the role of germline DNA damage repair gene mutations (gDDRm) in de novo metastatic castration sensitive prostate cancer (mCSPC) cases to potentially guide therapy choices. This article focuses on the association between gDDRm status and time to castration resistance to determine the prognostic value of gDDRm in mCSPC cases receiving standard androgen deprivation treatment‐based therapies.